Simulation of a turn on alpine skis - Nordt, A. A.; Springer, G. S.; Kollar, L. P. (Sports Engineering, 1999)
A model was developed to calculate the turning characteristics of alpine skis. The skis considered are constructed of layers of materials which may include wood, foam, metal, plastics and fibre-reinforced composites. The ski may be manufactured with or without camber and sidecut. The model simulates the motion of a skier of given height, weight and skill level travelling down a smooth slope while executing a constant radius turn. On the basis of the model a computer code was written which generates the time required for the skier to complete the turn. The model and corresponding computer code were verified by comparing the output of the code to data generated by skiers executing turns on a hill. The results of the model and the data were in good agreement. Using the computer code, the effects of design on the ski`s performance were examined. First, the times required for a skier to complete a turn were calculated, either on K2 Four 188 skis or K2 GS Race 204 skis. Second, the role of sidecuts in the performance of alpine skis was examined by calculating the times taken to complete a turn on K2 Four 188 skis with various sidecuts. In addition, table top experiments were performed with 59 cm long ski models placed on sand to visualize the interaction between the ski and the snow, and the manner in which sidecuts facilitate turns.